2020
DOI: 10.37722/apctm.20204
|View full text |Cite
|
Sign up to set email alerts
|

Health Beliefs and Perceptions: Implications for Type 2 Diabetes Self-Management

Abstract: Diabetes is a major public health menace across the globe and it is associated with physical, emotional and socioeconomic consequences. Existing literature supports the use of diabetes education as a tool to minimize the impact of the medical condition. However, the current figure revealed that beliefs and perceptions of patients may constitute a barrier to attendance. This paper provides insight into the impact of patient's perceptions and beliefs on attendance at diabetes education centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…3 Thus, diabetes has a negative physical, psychological, social, and economic impact on the affected individual. 5 Despite significant advancements in diabetes care, there has been a global upsurge in the prevalence of diabetes within the last decade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Thus, diabetes has a negative physical, psychological, social, and economic impact on the affected individual. 5 Despite significant advancements in diabetes care, there has been a global upsurge in the prevalence of diabetes within the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicated that barriers to attendance at diabetes education centres are due to various factors, such as demographic characteristics of the patient and organisation of care. [5][6][7] The individual is unique, with varying socio-demographic characteristics that may either influence or hinder attendance. Although some studies have identified the socio-demographic characteristics of nonattenders, there is little research to discern whether these factors can be used to predict attending behaviour.…”
Section: Introductionmentioning
confidence: 99%